Transarterial Embolization as a First-Line Treatment for Ruptured Renal Angiomyolipoma: A Case Report - Wicaksono, Krishna Pandu (http://dharmais.co.id/, 2026)
Introduction: Angiomyolipoma (AML) is a benign renal tumor that can be accompanied by potentially life-threatening spontaneous retroperitoneal hemorrhage when it becomes large. Prompt management is crucial. Treatment options for ruptured renal AML include surgical intervention and embolization, with transarterial embolization (TAE) increasingly recognized for its renal-sparing advantage and reduced invasiveness. We describe a case effectively managed with emergency TAE, highlighting its safety and efficacy.Case Presentation: A 57-year-old male was admitted for evaluation of hematuria, right flank pain, abdominal distension, and dyspnea. His condition was complicated by severe anemia and declining renal function, with eGFR of 28.1 mL/min/1.73 m². CT-scan angiography demonstrated a large retroperitoneal hematoma and a pseudoaneurysm, 3.5 × 4.0 × 6.0 cm, at the upper pole of the right kidney, arising from an interlobar artery. Multiple bilateral angiomyolipomas were also shown. An emergency transarterial embolization was performed using polyvinyl alcohol (PVA) particles to devascularize hypervascular lesions and detachable coils to occlude the pseudoaneurysm. Further embolization was also performed in the mid-segment, resulting in the complete resolution of lesions while maintaining the functional renal parenchyma. Clinical improvement was evident during a two-day follow-up, as indicated by an increase in hemoglobin levels, resolution of hematuria, and relief of abdominal symptoms.Conclusion: This case supports the role of TAE as an effective and organ-preserving treatment for ruptured renal AML.